حضور التصور الفوكوي في الفكر العربي المعاصر - شاكر مخلوف (My University, 2018)
لقد كانت تأثيرات فوكو متعددة الجوانب بتعدد الحقول التي خاض فيها بالبحث والتنقيب، حيث عرفت مفاهيمه تطبيقات مختلفة في التراث والحداثة، والحاضر والمعرفة والسلطة والعقل والنقد، حيث نجد عند آركون مفاهيم مثل: نظام الخطاب والسلطة والعقل والمفكر فيه، واللامفكر فيه والمستحيل التفكير فيه، وذلك في مشروعه لنقد العقل الإسلامي، وعند إدوارد سعيد في مسألة المثقف والسلطة، وعند التريكي مفهوما كاملا للفلسفة باعتبارها تشخيصا للواقع في إطار تأسيسه للفلسفة الشريدة، وعند مطاع صفدي مسألة الآخر ونقد الحداثة الغربية، وعند الجابري مفاهيم مثل الخطاب والإبستيمية في إطار مشروع نقد العقل العربي، وهو ما يؤكد حضور ميشيل فوكو القوي في الدراسات العربية المعاصرة. Abstract Foucault's impacts have been multifaceted as the multitude of fields in which he researched and explored. His concepts have known different applications in Heritage, Modernity, Present, Knowledge, Authority, Reason, as we find with Arcon concepts such: System of Discourse, Authority, Reason, what's thought of, what's not thought of, and the impossible to think of in his Criticising the Islamic reason project. For Edward Said's issue of the Intellectual and Authority, for Triki, a perfect concept to philosophy considering it a diagnosis for reality in the sense of his establishment of Houseless philosophy , and for Mutaa Safadi, the question of the Other and criticism of Western modernity , and for Jabri's concepts such as discourse and Epistemology in the sense of criticizing Arab Mind project, which confirms Michel Foucault's strong presence in contemporary Arabic studies. Keywords: knowledge, Authority, Criticism, Heritage, Modernity, Present, Discourse.
Keywords: المعرفة ; السلطة ; النقد ; التراث ; الحداثة ; الحاضر ; الخطاب، الأركيولوجيا، الإبستيمي